SIGNIFICANCE OF FEEDBACK ON WRITING PERFORMANCE OF STUDENTS (Scientific journal of the Fergana State University, 2023)
The article deals with the questions how to develop students’ motivation to learn foreign languages via giving feedback to writing of the students. Its main purpose is to find the most appropriate and effective ways out. The paper presents the analytical review of research on the problems concerning building and development of educational motivation, describes its types and highlights varieties that are specific to foreign language learning. The paper offers examples how to use feedback effectively while teaching foreign languages.